##common.prefixAndTitle.tip## IMPLEMENTATION OF TAMAN BACA PROGRAM TO INCREASE CHILDREN'S INTEREST IN READING IN KALIKOA VILLAGE - Salma Aufie Khumairoh; Umi Hani; Ahmad Faozan; Syukron Ma’mun; Achmad Nurjannah (Al Naqdu, 2023)
The habit of reading must be instilled from an early age to increase children's horizons. Reading will train children to be more sensitive, active and creative. In this case the motivation to read is needed to encourage someone to love reading. However, in motivating children to like reading, there are often problems with the availability of reading facilities. The implementation method used in this service is the method of providing reading gardens and reading habits. The target of the program is the community, especially children who live in Kalikoa Village. The reading garden program begins with a survey of locations that are easily accessible to readers in Kalikoa Village, especially children who need a variety of reading sources to enrich their scientific treasures. The results of this community service activity are a solution to the lack of access and reading facilities and become one of the efforts to increase children's interest in reading in Kalikoa Village. Motivation to read is very necessary to encourage someone to love reading. However, in motivating children to like to read, there are often problems with the availability of reading facilities. The absence of facilities and infrastructure to increase children's interest in reading is the reason for the establishment of a reading park that can be used for the surrounding community. Reading gardens can broaden the horizons of its users and serve as a medium for lifelong learning.